The Influence of Visual, Auditory, Kinesthetic (VAK) Learning Methods in Enhancing English Vocabulary for Students at MTs Nur-Rahma Kota Bengkulu - Nuriska, Nuriska; Zasrianita, Fera; Revola, Yashori (The Future of Education Journal, 2025)
This study aims to determine the effect of the Visual, Auditory, Kinesthetic (VAK) Learning method on the English vocabulary mastery of seventh-grade students at MTs Nur Rahma Kota Bengkulu. The research method used was quantitative with a pre-experimental design (One-Group Pretest-Posttest Design). The subjects of this study were 14 students of class VII Mekkah. Data were collected through vocabulary tests (pre-test and post-test) and analyzed using the Normality Test and Paired Sample t-Test with the assistance of SPSS version 27. The results of the study showed a significant improvement in students’ vocabulary mastery after the implementation of the VAK method. This was evidenced by the average post-test score (61.57) being higher than the average pre-test score (41.43), as well as the result of the paired sample t-test with a significance value (2-tailed) of 0.001 < 0.05. Therefore, it can be concluded that the Visual, Auditory, Kinesthetic (VAK) Learning method is effective in improving the English vocabulary mastery of seventh-grade students at MTs Nur Rahma Kota Bengkulu. g Methods in Enhancing English Vocabulary for Students at Mts Nur-Rahma Kota Bengkulu